Honor - Shafak, Elif (London Penguin Books, 2013)
Leaving her twin sister behind, Pembe leaves Turkey for love - following her husband Adem to London. There the Topraks hope to make new lives for themselves and their children. Yet, no matter how far they travel, the traditions and beliefs the Topraks left behind stay with them - carried in the blood.
Keywords: Kurds -- Social conditions -- Twins